A Multiagent System for Dynamic Data Aggregation in Medical Research. - Dubovitskaya, Alevtina; Urovi, Visara; Barba, Imanol; Aberer, Karl; Schumacher, Michael Ignaz (BioMed Research International, 2016)
The collection of medical data for research purposes is a challenging and long-lasting process. In an effort to accelerate and facilitate this process we propose a new framework for dynamic aggregation of medical data from distributed sources. We use agent-based coordination between medical and research institutions. Our system employs principles of peer-to-peer network organization and coordination models to search over already constructed distributed databases and to identify the potential contributors when a new database has to be built. Our framework takes into account both the requirements of a research study and current data availability. This leads to better definition of database characteristics such as schema, content, and privacy parameters. We show that this approach enables a more efficient way to collect data for medical research.